2012
DOI: 10.1073/pnas.1119598109
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the psychedelic state as determined by fMRI studies with psilocybin

Abstract: Psychedelic drugs have a long history of use in healing ceremonies, but despite renewed interest in their therapeutic potential, we continue to know very little about how they work in the brain. Here we used psilocybin, a classic psychedelic found in magic mushrooms, and a task-free functional MRI (fMRI) protocol designed to capture the transition from normal waking consciousness to the psychedelic state. Arterial spin labeling perfusion and blood-oxygen leveldependent (BOLD) fMRI were used to map cerebral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
870
4
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 872 publications
(939 citation statements)
references
References 45 publications
51
870
4
14
Order By: Relevance
“…A recent fMRI study, however, reported an overall decrease of brain activity in the medial frontal cortex after intravenous administration of psilocybin (Carhart-Harris et al, 2012). Notably, the reported decrease correlates with a suppression of the DMN (Buckner et al, 2008).…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 98%
“…A recent fMRI study, however, reported an overall decrease of brain activity in the medial frontal cortex after intravenous administration of psilocybin (Carhart-Harris et al, 2012). Notably, the reported decrease correlates with a suppression of the DMN (Buckner et al, 2008).…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 98%
“…Altogether, the effects of LSD on PPI in normal humans were consistent with both the PPI deficits after LSD administration in animals and sensorimotor gating deficits in schizophrenia patients. have not yet been studied using LSD in neuroimaging studies, in contrast to several modern investigations that used psilocybin to model psychotic states (24,25).…”
Section: Sensorimotor Gating Of the Acoustic Startle Responsementioning
confidence: 99%
“…Many studies also sought to describe the psychotomimetic effects of LSD but were not designed to measure any positive subjective effects. Modern experimental studies with hallucinogens in humans resumed in the 1990s with N-N-dimethyltryptamine (DMT, ayahuasca) (18)(19)(20)(21), ketamine (21)(22)(23), and psilocybin (24,25) but not with LSD. Both LSD and psilocybin have also been recently evaluated in pilot therapeutic studies as treatments for anxiety in patients with lifethreatening diseases (11,26).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of activity decrease in the ACC and medial prefrontal cortex (mPFC) was proportional to the intensity of the subjective "unitive" effect (Carhart-Harris et al, 2012), suggesting the reduction of activity to these inhibitory hub regions enables a state of unrestrained associative and perceptual faculties. These fMRI studies of psilocybin's specific neurological correlates is certainly important and still ripe for interpretation, and certainly give us valuable hints as to the neurophysiology at play during the Mazatec shaman's intentioned transition into specific non-ordinary states of consciousness.…”
Section: Cognitive Models Of Transcendencementioning
confidence: 99%
“…This sudden surge of priming volume measured in the psilocybin experience (Spitzer et al, 1996) can be conceptualized as a flooding inlet of attention; the pupils dilating in a state of hyperawareness and hypervigilance, the whole nervous system buzzing with vibrant sensation, the eyes allowing more light information to shine inwards from the surroundings, spurring neuronal activation and reducing cerebral bloodflow (Carhart-Harris et al, 2012) to areas of the brain responsible for latent inhibition (LI), or the filtering down of sensory information from conscious awareness. .…”
Section: Munn's "Wellsprings Of Meaning"mentioning
confidence: 99%